High Resolution Imaging of DNA Methylation Dynamics using a Zebrafish Reporter - Ranran Zhang (Nature Portfolio, 2017)
Abstract As one of the major epigenetic modifications, DNA methylation is constantly regulated during embryonic development, cell lineage commitment, and pathological processes. To facilitate real-time observation of DNA methylation, we generated a transgenic zebrafish reporter of DNA methylation (zebraRDM) via knockin of an mCherry-fused methyl-CpG binding domain (MBD) probe driven by the bactin2 promoter. The probe colocalized with heterochromatin, and its intensity was positively correlated with 5 mC immunostaining at a subcellular resolution in early embryos. Biochemical assays indicated that cells with stronger fluorescence maintained a higher level of DNA methylation, and time-lapse imaging at the blastula stage showed that the level of DNA methylation was transiently strengthened during mitosis. By crossing zebraRDM with other fluorescent transgenic lines, we demonstrate that the reporter can visually distinguish different cell lineages in organs like the heart. Our zebraRDM reporter therefore serves as a convenient and powerful tool for high-resolution investigation of methylation dynamics in live animals.